2015
DOI: 10.3109/17435390.2015.1107145
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of two different copper oxide nanomaterials in sea urchin (Lytechinus pictus) embryos

Abstract: Copper oxide nanomaterials (nano-CuOs) are widely used and can be inadvertently introduced into estuarine and marine environments. We analyzed the effects of different nano-CuOs (a synthesized and a less-pure commercial form), as well as ionic copper (CuSO 4 ) on embryo development in the white sea urchin, a well-known marine model. After 96 h of development with both nano-CuO exposures, we did not detect significant oxidative damage to proteins but did detect decreases in total antioxidant capacity. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 75 publications
(97 reference statements)
2
33
0
Order By: Relevance
“…Conversely, while nCuO did not cause changes in mitochondrial membrane potential (MMP), CuSO 4 significantly (p < 0.05) decreased MMP even at 1 mg/L. Interestingly, nCuO (≥ 500 μg/L) and CuSO 4 (≥200 μg/L) acted as a chemosensitizers and increased the developmental toxicity of vinblastine, a cell division inhibitor (Torres-Duarte et al, 2016;Wu et al, 2015).…”
Section: High Throughput/content Screening Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, while nCuO did not cause changes in mitochondrial membrane potential (MMP), CuSO 4 significantly (p < 0.05) decreased MMP even at 1 mg/L. Interestingly, nCuO (≥ 500 μg/L) and CuSO 4 (≥200 μg/L) acted as a chemosensitizers and increased the developmental toxicity of vinblastine, a cell division inhibitor (Torres-Duarte et al, 2016;Wu et al, 2015).…”
Section: High Throughput/content Screening Studiesmentioning
confidence: 99%
“…However, stability of nCuO is strongly influenced by salinity and pH (Conway et al, 2015a;Torres-Duarte et al, 2015;Gomes et al, 2011;Buffet et al, 2013). Rapid aggregation and sedimentation of nCuO occurs at high IS (e.g.…”
Section: Environmental Fate Of Cu Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…been shown that smaller sized Cu particles tend to dissolve faster, and exhibit a higher toxic effect to aquatic organisms (Cai et al, 2005;Torres-Duarte et al, 2015).…”
Section: Conclusion and Environmental Implicationsmentioning
confidence: 99%
“…However, this classification of dissolved Cu lumps together dissolved ions, nanoparticles (generally defined as particles with at least one dimension between 1 and 100 nm) and some bulk particles (100e450 nm in size). For proper risk assessment, it is necessary to determine how much of these different fractions of Cu are leached from antifouling paints since their fate, bioavailability, and toxicity differ considerably (Bielmyer-Fraser et al, 2014;Shi et al, 2011;Siddiqui et al, 2015;Thit et al, 2013;Torres-Duarte et al, 2015).…”
Section: Introductionmentioning
confidence: 99%